2014
DOI: 10.1021/cb500798y
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Chemical Chaperones Based on Their Effect on Protein Folding Landscapes

Abstract: Various small molecules present in biological systems can assist protein folding in vitro and are known as chemical chaperones. De novo design of chemical chaperones with higher activity than currently known examples is desirable to ameliorate protein misfolding and aggregation in multiple contexts. However, this development has been hindered by limited knowledge of their activities. It is thought that chemical chaperones are typically poor solvents for a protein backbone and hence facilitate native structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 38 publications
0
58
0
Order By: Relevance
“…The use of chemical chaperones might lead to different effectso np roteins.T hus, in our case, 4-PBA resulted in increased levels of secretion of WT and mutant proteins and,c onversely,c ompound 5 promotes their degradation. [29] More interestingly,c ompound 5 does not directly affect the general proteasome activity.I na ddition, we exclude the possibility that compound 5 interferesw ith total protein synthesis by reducing the levels of NLGN3p roteins by inhibiting their synthesis. Thus,w ehypothesize that the reduction in the amount of both NLGN3 proteins may be associated with the potentiation of the ER quality control and folding machinery,a sw eh ave successfully showed by several methods.…”
Section: Resultsmentioning
confidence: 97%
“…The use of chemical chaperones might lead to different effectso np roteins.T hus, in our case, 4-PBA resulted in increased levels of secretion of WT and mutant proteins and,c onversely,c ompound 5 promotes their degradation. [29] More interestingly,c ompound 5 does not directly affect the general proteasome activity.I na ddition, we exclude the possibility that compound 5 interferesw ith total protein synthesis by reducing the levels of NLGN3p roteins by inhibiting their synthesis. Thus,w ehypothesize that the reduction in the amount of both NLGN3 proteins may be associated with the potentiation of the ER quality control and folding machinery,a sw eh ave successfully showed by several methods.…”
Section: Resultsmentioning
confidence: 97%
“…Beyond overexpression or constitutive activation of HSFs using genetic tools, increased HSR and HSP expression and protein folding can also be induced by a number of promising small chemical compounds. Trehalose, thought to act as a chemical chaperone, is able to stabilize polyQ proteins in their native conformation; however, it is also known to be an autophagy inducer (discussed below) . This compound was shown to be efficient in HD cellular and animal models and recently in SCA17 mice .…”
Section: Therapeutic Strategies For Polyq Diseasesmentioning
confidence: 99%
“…Study [24] proposed a classification for osmolytes based on their effect on the folding pathway of a mutant form of maltose-binding protein (DM-MBP). The authors of this study identified two distinct groups of osmolytes: osmolytes of group I (TMAO and trehaloze) that affect the entropic component of the free energy barrier between the native and unfolded states of DM-MBP, while, osmolytes of group II (proline and serine) mainly affect the enthalpy component of the free-energy barrier.…”
Section: Osmolytes Of Class II Increase (mentioning
confidence: 99%
“…This indicates that the entropy contribution to the induced renaturation of proteins in osmolyte solutions can be significant [94][95][96][97]. Studies [24,98] investigated the renaturation of a slowly folding mutant of a maltosebinding protein in vivo and in vitro. The authors of these reports showed that various osmolytes change the folding path of this protein in different ways.…”
Section: Protein Folding In Osmolyte Solutionsmentioning
confidence: 99%